Prevalence and safety of diazoxide in the neonatal intensive care unit. (November 2018) - Gray, Keyaria; Dudash, Kathryn; Escobar, Carla; Freel, Colman; Harrison, Tylah; McMillan, Chandler; Puia-Dumitrescu, Mihai; Cotten, C.; Benjamin, Robert; Clark, Reese; Benjamin, Daniel; Greenberg, Rachel
Abstract Objective Diazoxide is used to treat infants with persistent hypoglycemia, but the prevalence of its use and adverse effects are not well described. We report demographic and clinical characteristics of infants treated with diazoxide in neonatal intensive care units (NICUs). Study design Retrospective cohort study of infants 24–41 weeks' gestation admitted to 392 NICUs from 1997–2016, comparing characteristics between hypoglycemic infants exposed/not exposed to diazoxide. For diazoxide courses > 1 day, we report percentages of infants starting diuretics and/or developing new ventilator/oxygen requirement during therapy. Results Among 1, 249, 466 infants, 185, 832 had hypoglycemia; 1066/185, 832 (0.57%) received diazoxide. Diazoxide use increased over time (P  = 0.001). Infants receiving diazoxide varied from 0–14.9% among centers. New diuretic courses were associated with 91/664 (14%), and new oxygen or ventilator requirement during therapy was associated with 64/556 (12%) and 34/647 (5%), respectively. Conclusions Diazoxide use in NICU settings has increased over time. Infants receiving diazoxide commonly received diuretics.